FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STRES KERJA PADA KARYAWAN BAGIAN KEPESERTAAN DI BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN UNGARAN - Feby Ansari Mayang S.; Daru Lestantyo; Bina Kurniawan (Jurnal Kesehatan Masyarakat (Undip), 2018)
Occupational Stress are the condition of physical or mental that came under pressure due to task demands that not compatible with worker’s ability. Any work have occupational stress as hazard including working as employees in health care security. The purpose of this research was to analyze factors that related to occupational stress. The design of this study was explanatory research with cross-sectional approach. Population in this research was 30 employees of National Health Care Security (BPJS) Ungaran. Questionnare was used as an instrument in this research. The measurement of occupational stress was assessed by GHQ-12 questionnnare. Statistical analysis used was chi-square test. The result of the research showed that there was a relation between task demands (p=0,011) and individual role in organization (p=0,010) with occupational stress, while there was no relation between age (p=0,526), work period (p=0,151) career development (p=0,127), organizational structure and climate (p=0,825), and occupational relations (p=0,351) with occupational stres. Researchers suggest company to provide socialization of risk and transparency of decision making in problem solving to their employees.